Chapter Measuring logical competences and soft skills when enrolling in a university degree course - Bertaccini, Bruno (Proceedings e report, 2021)
Logical abilities are a ubiquitous ingredient in all those contexts that take into account soft skills, argumentative skills or critical thinking. However, the relationship between logical models and the enhancement of these abilities is rarely explicitly considered. Two aspects of the issue are particularly critical in our opinion, namely: (i) the lack of statistically relevant data concerning these competences; (ii) the absence of reliable indices that might be used to measure and detect the possession of abilities underlying the above-mentioned soft skills. This paper aims to address both aspects of this topic by presenting the results of a research we conducted in the period October - December 2020 on students enrolled in various degree courses at the University of Florence. To the best of our knowledge, to date this is the largest available database on the subject in the Italian University System. It has been obtained by a three-stage initiative. We started from an "entrance" examination for assessing the students' initial abilities. This test comprised ten questions, each of which was centered on a specific reasoning construct. The results we have collected show that there is a widespread lack of understanding of basic patterns that are common in the everyday way of arguing. Students then underwent a short training course, using formal logic techniques in order to strengthen their abilities, and afterwards took an "exit" examination, replicating the structure and the questions difficulty of the entrance one in order to evaluate the effectiveness of the course. Results show that the training was beneficial.